2016
DOI: 10.1167/16.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Perceived azimuth direction is exaggerated: Converging evidence from explicit and implicit measures

Abstract: Recent observations suggest that perceived visual direction in the sagittal plane (angular direction in elevation, both upward and downward from eye level) is exaggerated. Foley, Ribeiro-Filho, and Da Silva's (2004) study of perceived size of exocentric ground extent implies that perceived angular direction in azimuth may also be exaggerated. In the present study, we directly examined whether perceived azimuth direction is overestimated. In Experiment 1, numeric estimates of azimuth direction (−48° to 48° rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 57 publications
(148 reference statements)
6
22
0
Order By: Relevance
“…This is because the magnitude of the allocentric component for the three larger poles (i.e., 1.2 or ~20%) is quantitatively consistent with prior estimates of the difference in gain between the angular expansion gain for perceived elevation (1.5; Durgin & Li, 2011) and the angular expansion gain for perceived azimuth measured when the retinotopic HVI is taken into account (1.25; Li & Durgin, in press). That is, 1.5 divided by 1.25 equals 1.2, which predicts a 20% overestimation of height compared to width.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This is because the magnitude of the allocentric component for the three larger poles (i.e., 1.2 or ~20%) is quantitatively consistent with prior estimates of the difference in gain between the angular expansion gain for perceived elevation (1.5; Durgin & Li, 2011) and the angular expansion gain for perceived azimuth measured when the retinotopic HVI is taken into account (1.25; Li & Durgin, in press). That is, 1.5 divided by 1.25 equals 1.2, which predicts a 20% overestimation of height compared to width.…”
Section: Discussionsupporting
confidence: 81%
“…Asymmetric directional distortions can be used to quantitatively model downhill slope exaggeration (Li & Durgin, 2009), as well as a variety of ground-extent anisotropies (Durgin & Li, 2011, Foley et al, 2004; Li et al, 2011; Li et al, 2013; Li & Durgin, in press). Thus, the present study used mathematical modeling based on non-verbal techniques of parameter estimation to extend the explanatory scope of the AEH to the large-scale HVI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present experiment, we presented a fixed reference ball at the top of a narrow pole that was positioned either very close, in depth, to the farthest ground target or far beyond it. If the distance in depth between the target and the reference is what primarily produces contamination, then angular estimates for the farthest targets (smallest angles) should differ as a function of the whether the 3D distance to the reference ball is small or large (see also Li & Durgin, 2016 , for a similar effect in judgments of azimuth).…”
Section: Experiments 4: Manipulating the Distance To The Reference Poimentioning
confidence: 99%
“…He observed that the perceived visual angle for large-scale vertical extents was greater than that for horizontal extents in a manner that might account for the large-scale horizontal-vertical illusion (HVI) [2,3,4]; Li and Durgin discovered that exaggeration in downhill slant perception was amplified by conditions that yoked it to an exaggerated perception of downward gaze direction or angular declination [5]. Durgin and Li ultimately showed that these exaggerations in perceived angular declination could quantitatively account for long-standing observations of explicit ground distance underestimation [6,7,8]. Indeed, Foley and colleagues [9] had interpreted underestimates of ground distance using the assumption that the effective (but not perceived) angular size of the ground extents, from the point of observation, was differentially exaggerated in azimuth and in elevation.…”
Section: Introductionmentioning
confidence: 99%